PENGEMBANGAN PERALATAN PRAKTIKUM PADA MATAKULIAH FISIKA KEBUMIAN LANJUT - Nur Islami (Jurnal Pendidikan, 2018)
One of the courses in the Physics Education Study Program that requires direct observation in the field is Advanced Earth Physics. In this course there is one subject that discusses about Groundwater. This study aims to develop a geoelectrical resistivity equipment that can be used in field work by students of the Riau University Physics Education Study Program. The method used was the Research and Development method. The need for tools was analyzed so that ideas for making tools emerge. The tool is designed in such a way as to consider the level of safety, ease of use and antil the acuracy. The results showed that the tools developed were successfully made well. The equipment was validated by experts and field tested. Four experts of Physics lecturers gave an average rating of 3.7on a scale of 4. Thus this tool can already be used in Advanced Earth Physics lectures in the Physics Education Study Program at the University of Riau.